2019
DOI: 10.1002/1878-0261.12457
|View full text |Cite
|
Sign up to set email alerts
|

Mutual regulation of MDM4 and TOP2A in cancer cell proliferation

Abstract: MDM 4 and topoisomerase II α ( TOP 2A) are overexpressed in various human cancers. MDM 4 acts as an oncoprotein which promotes cancer progression by inhibiting tumor suppressor p53. As a DNA replication‐ and cell division‐regulating enzyme, TOP 2A is the main target of many anticancer therapy regimens; however, the exact role of TOP 2A in cancer remains elusive. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Conditioned medium of cancer cell lines was prepared as described previously (47). OS cell lines (MG63, U-2 OS, Saos-2, 143B, K2M2 and DLM8) were incubated in DMEM containing 10% FBS until the cells reached 80% confluence at 37°C.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…Conditioned medium of cancer cell lines was prepared as described previously (47). OS cell lines (MG63, U-2 OS, Saos-2, 143B, K2M2 and DLM8) were incubated in DMEM containing 10% FBS until the cells reached 80% confluence at 37°C.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…TOP2A serves an important role in various biological behaviors of cells, including DNA replication, chromosome separation, chromatin concentration and gene expression ( 49 ). As a DNA replication- and cell division-regulating enzyme, TOP2A is the main target of several anticancer drugs, such as doxorubicin, etoposide, and mitoxantrone ( 50 ). High expression levels of TOP2A in various types of tumors, such as lung adenocarcinoma, bladder urothelial carcinoma, breast, prostate and colon cancer, indicates a poor prognosis ( 51 – 55 ), although this has not been previously reported in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…TOP2A is one of the nuclear matrix components. It has been found that overexpression of TOP2A is closely related to breast cancer, prostate cancer and liver cancer [19,20]. In normal tissues, PTTG1 is expressed in low amounts or not at all in normal tissue.…”
Section: Discussionmentioning
confidence: 99%